2017
DOI: 10.1038/srep46066
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcome analysis of 6325 burn patients: a five-year retrospective study in a major burn center in Southwest China

Abstract: Burns are a major cause of injury worldwide. We investigated the epidemiology and outcomes of burn patients in a major burn center in southwest China between 2011 and 2015 to provide guidance for burn prevention. Of the 6,325 included burn patients, 66.8% were male and 34.7% were 0 ~ 6 years old. The incidence of burns peaked in autumn. Scald was the most common cause of burns, which was predominant in patients aged 0 ~ 6 years. The mean total body surface area (TBSA) of burns was 13.4%, and patients with burn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
73
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 32 publications
17
73
1
8
Order By: Relevance
“…Unlike the injuries caused by other types of causes like the flame or scald burns, electrical causes tend to have lesser TBSA and as we can see in our findings as well as those in Southwest China. 17 In this Chinese report, first, 95.5% of electrical injury resulted in full thickness burns which also corresponds to our findings of 86.1%. 17 Second, they reported that majority of their patients who sustained full thickness electrical injury were in less than or equal to 5% TBSA group, that is, 76.01%.…”
Section: Jssn 2017; 20 (2)supporting
confidence: 90%
See 2 more Smart Citations
“…Unlike the injuries caused by other types of causes like the flame or scald burns, electrical causes tend to have lesser TBSA and as we can see in our findings as well as those in Southwest China. 17 In this Chinese report, first, 95.5% of electrical injury resulted in full thickness burns which also corresponds to our findings of 86.1%. 17 Second, they reported that majority of their patients who sustained full thickness electrical injury were in less than or equal to 5% TBSA group, that is, 76.01%.…”
Section: Jssn 2017; 20 (2)supporting
confidence: 90%
“…Some have reported lesser hand injuries in flame and scald injuries but with respect to electrical injuries where most of the injury are located over the upper limbs. 17 Our study also has similar findings. Unlike the injuries caused by other types of causes like the flame or scald burns, electrical causes tend to have lesser TBSA and as we can see in our findings as well as those in Southwest China.…”
Section: Jssn 2017; 20 (2)supporting
confidence: 87%
See 1 more Smart Citation
“…This is not seen in usual burn injuries. Haisheng Li et al 23 showed an incidence of 40.1% of full thickness burn and that too was mainly due to flame. Patients with full thickness burn require operative intervention.…”
Section: Severity Of Burnmentioning
confidence: 99%
“…Sometimes burns sustained are only on the face due to sudden fall over the burn agent. Haisheng Li et al 23 also mentioned that limbs were the most common burn sites accounting for 72.1% of all admissions. Yao Y et al 25 obtained that 31.98% of victims involved multiple body site burns in terms of injured body region.…”
Section: Site Of Burnmentioning
confidence: 99%